ANALISIS FAKTOR YANG MEMPENGARUHI MINAT MAHASISWA TERHADAP PEMILIHAN KARIR AKUNTAN/ NON AKUNTAN - Yusran, Rio Rahmat (Jurnal Akuntansi (Media Riset Akuntansi & Keuangan), 2017)
Promising a great career and a dream of every student. Judging from the economicdevelopment impact on the number of firms in Indonesia in line with the highdemands of the working world. Many of the companies that give effect to the studentas a job-seeker in terms of career choice. Determining career working world isinfluenced by several factors. This study analyzes the factors that influence studentsin career selection accountants and non-accountants. There are also several factorsin this study was measured by financial rewards, training and professionalrecognition as determining career choice of accountants and non-accountants.Samples and objects that are used are the students / i who work or who haveworked in the area of Batam. The results of this study indicate that factors affectingthe students as measured by financial rewards, professional training andprofessional recognition partially with significant value less than 0.05. This showsthat the factor of financial rewards, professional training and professional recognitionhas an influence on career choice accountant / non accountants. Whilesimultaneously financial rewards, professional training and professional recognitionaffect the career accountant / non-accountants with significant value less than 0.05.